2013
DOI: 10.1007/s00586-013-2712-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes following anterior foraminotomy for one- or two-level cervical radiculopathy

Abstract: Purpose Anterior foraminotomy (AF) is a surgical treatment for unilateral cervical radiculopathy that avoids fusion-related complications, but its long-term outcome has yet to be investigated. To clarify the efficacy of AF, the author retrospectively collected long-term data regarding the results of this technique. Methods Of 50 patients who underwent AF between November 1999 and June 2005, those who were followed for more than 6 years (n = 44) were enrolled in this study. The parameters studied included the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 33 publications
2
24
0
3
Order By: Relevance
“…Further, due to extraordinary advances in microsurgery techniques, allowing care and treatment of cervical radiculopathy, microsurgery of the cervical spine has become a focus of research. An increasing number of studies reported little trauma, reduced blood loss, shorter hospital stays faster recovery times and safety and reliability as advantages via microendoscopic foraminotomy [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Further, due to extraordinary advances in microsurgery techniques, allowing care and treatment of cervical radiculopathy, microsurgery of the cervical spine has become a focus of research. An increasing number of studies reported little trauma, reduced blood loss, shorter hospital stays faster recovery times and safety and reliability as advantages via microendoscopic foraminotomy [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…We think that operated segment might be more degenerated to fuse eventually because of the previous advanced spondylosis and the progressive bony regrowth in the foraminotomy site. Park et al14) reported similar results for the ROM and the disc height of operated segment after ACMF in long-term study. They reported that 40 of 43 operated segments (93%) were defined as degenerated in their study, which was larger than our study (30%).…”
Section: Discussionmentioning
confidence: 52%
“…E para pacientes com problemas na região cervical encontramos médias menores do que 19% (PARK, et al, 2013, CARR et al, 2011.…”
Section: é T O D O | 40unclassified
“…E neste período foram realizados tratamentos conservadores, como: fisioterapia e utilização de medicamentos, porém os pacientes não obtiveram resultados positivos e então seus médicos optaram pelo tratamento cirúrgico (CARR et al, 2011;LEITE et al;KRISHNA, et al, 2014;PARK, et al, 2013;YOSHINO;RODRIGUES, 2012).…”
Section: é T O D O | 40unclassified
See 1 more Smart Citation